Electromechanical machinery theory and performance - Ortmeyer, Thomas (IOP (Series). Release 5., 2018)
Electromechanical Machinery Theory and Performance presents a detailed explanation of electromagnetic machines, giving specific focus on transformers and AC rotating machines that can be used in the preservation and transference of energy and power. This book is developed for students at both the graduate and undergraduate level and can be used for practicing engineers as well. The book explores different machines, transformers and converters that have become an essential part in the efficient use of both energy and power. The book includes examples and numerical exercises that will enable students and practicing engineers to efficiently practice and use certain calculations. Aimed as a one semester course, this book gives a detailed analysis of modern machines and their application.